2009
DOI: 10.1038/jhg.2009.130
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of a novel mutated allele of the OCA2 gene associated with high incidence of oculocutaneous albinism in a Polynesian community

Abstract: Oculocutaneous albinism type 2 (OCA2) is a human autosomal-recessive hypopigmentation disorder associated with pathological mutations of the OCA2 gene. In this study, we investigated a form of OCA in a Polynesian population with an observed phenotype characterized by fair skin, some brown nevi present in the sun-exposed areas and green or blue eyes. Hair presented with a unique red coloration since birth, with tones ranging across individuals from Yellow-Red to Brown-Red, or Auburn. We genetically screened for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…This allele has a frequency of 0.26 on the Solomon Islands and is not seen outside of Oceania, so it represents a very recent evolutionary event, with the allele acting in a recessive manner [81]. Similarly, a very high frequency of a population-specific OCA2 mutation causing the expression of a full albinism phenotype has been found in the Polynesian Islands [82]. Both are cases of genetic drift resulting from population founder effects (Box 1).…”
Section: Human Pigmentation Genes With Signs Of Selection Pressurementioning
confidence: 99%
“…This allele has a frequency of 0.26 on the Solomon Islands and is not seen outside of Oceania, so it represents a very recent evolutionary event, with the allele acting in a recessive manner [81]. Similarly, a very high frequency of a population-specific OCA2 mutation causing the expression of a full albinism phenotype has been found in the Polynesian Islands [82]. Both are cases of genetic drift resulting from population founder effects (Box 1).…”
Section: Human Pigmentation Genes With Signs Of Selection Pressurementioning
confidence: 99%
“…The novel mutation rs387907171 * C/T occurred at a frequency of 26% in the Solomon Islands but was absent outside Oceania. In contrast, TYRP1 was excluded as being the gene responsible for a form of OCA in a Polynesian population in another study [58] . It is notable that at the same position there is a C93H polymorphism present at 1.1% frequency in the European population [60] , but an association with a pigmentation phenotype is yet to be examined.…”
Section: Oca2: the Major Gene For Eye Colour And Albinism Type IImentioning
confidence: 99%
“…TYRP1 can act to stablise the TYR protein and form heterodimeric complexes within the melanosome [57] . It was found that 95% of OCA3-related mutations result in the generation of premature stop codons or frameshifts producing truncated proteins, red-toned hair, reddish-brown pigmented skin and optical features not as severe as in other forms of OCA [58] . Only 5 mutations have been described so far in TYRP1 [39] .…”
Section: Oca2: the Major Gene For Eye Colour And Albinism Type IImentioning
confidence: 99%
“…Many of these genes are focused on melanosome biosynthesis and transport and regulation of melanocytes and melanosomes. For example, the red hair color phenotype is controlled by MC1R, and the most common cause of albinism in Europeans is linked to OCA2 [ 78 ] . Two other important genes for albinism, an autosomal recessive disorder, are SLC45A2 and SLC24A5 [ 78 ] .…”
Section: Genes That Control Skin Colormentioning
confidence: 99%
“…For example, the red hair color phenotype is controlled by MC1R, and the most common cause of albinism in Europeans is linked to OCA2 [ 78 ] . Two other important genes for albinism, an autosomal recessive disorder, are SLC45A2 and SLC24A5 [ 78 ] . Sabeti et al used three different forms of long-range haplotype analysis to determine gene under positive selection in the genome of European individuals [ 79 ] .…”
Section: Genes That Control Skin Colormentioning
confidence: 99%